Biogeography and community structure of fishes in South African estuaries - Harrison, Trevor D (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2003)
The biogeography and community structure of the fishes of South African estuaries was investigated. In all, 109 systems were examined representing two broad types: temporarily closed and permanently open estuaries. Multivariate analyses of the fish communities identified three biogeographic regions. A cool-temperate region extended along the west and southwest coasts; a warmtemperate zone stretched along the south, southeast and east coasts and a subtropical region occurred along the east coast. The boundaries of these biogeographic regions were also delineated. The general physico-chemical characteristics of the estuaries within the three biogeographic regions also reflected regional differences in climate, rainfall and ocean conditions. Estuarine temperatures followed the trend for marine coastal waters, decreasing from subtropical estuaries toward cool-temperate systems. The low rainfall and runoff in the warm-temperate region together with high evaporation rates and strong seawater input resulted in higher salinities in these estuaries. These factors also accounted for the predominantly clearer waters in warm-temperate estuaries. The estuaries in the three biogeographic regions were also shown to contain somewhat distinctive fish assemblages. Temperature and salinity appeared to be the two main factors affecting the distribution and abundance of fishes in South African estuaries. Subtropical systems were characterised by fishes mostly of tropical origin as well as certain south coast endemic species. Warm-temperate estuaries were dominated by endemic taxa with some tropical species also present. The fish fauna of cooltemperate estuaries mostly comprised south coast endemic species with cosmopolitan and temperate taxa also present. Certain functional components of the ichthyofauna also exhibited slight differences between regions. Freshwater fishes were a major component of closed subtropical estuaries while estuarine resident species were more abundant in warm-temperate estuaries. Overall, estuarine-dependent marine species dominated the fish fauna of the estuaries in all biogeographic regions, signifying that South African estuaries perform a vital nursery function for this group of fishes. Slight differences were also apparent in the trophic structure of the fishes; these were related to environmental differences between regions. Zooplanktivores and fishes that feed on aquatic macrophytes/invertebrates assumed a relatively higher importance in warm-temperate systems. Overall, detritivores dominated the estuarine fish fauna in all regions, indicating that detritus forms the main energy source in South African estuaries.
Keywords: Estuarine ecology -- South Africa; Estuarine fishes -- South Africa; Fish communities -- South Africa; Biogeography -- South Africa